PEMIKIRAN PENDIDIKAN ISLAM DI SINGAPURA MENURUT MOHAMMAD HANIFF HASSAN - Bahar, Herwina; Anuar, Lathifah (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2016)
As a minority, the Muslim Malay Singaporeans should portray themselves as a progressive community and have a vision of a model society with an Islamic thinking which is distinctively Singaporean. The community needs to do so to understand contextual nature (al-waqiÃyah) within the general framework of the Islamic teaching. Besides, the community should hold firmly to practicing in moderation (al-wasathiyah) which is an important aspect in preserving stability among the community in the Malay Archipelago. Parallel to this, Muslim scholars in Singapore are making effort to achieve this objective. Among them is Muhammad Haniff Hassan who, in his capacity as a prominent scientist, has been actively contributing his ideas on various issues in the form for writing articles or giving talks at various forums. His topics varies from politics, economics, educations, social, etc.